Reviews of environmental contamination and toxicology - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2013)
CONTENTS Foreword Preface Microbial Transformation of Trace Elements in Soils in Relation to Bioavailability and Remediation Nanthi S. Bolan, Girish Choppala, Anitha Kunhikrishnan, Jinhee Park, and Ravi Naidu Biological Effects of Boron Mustafa Kabu and Murat Sirri Akosman Environmental Fate and Ecotoxicology of Fenpropathrin Emerson Kanawi et al, Robert Budd, and Ronald S. Tjeerdema Use of Land Snails (Pulmonata) for Monitoring Copper Pollution in Terrestrial Ecosystems Dragos V. Nica, Despina-Maria Bordean, Aurica Breica Borozan, Iosif Gergen, Marian Bura, and Ionut Banatean-Dunea Index